The sustainable development concept in the EU’s activity: an example of environmental priorities of Sustainable Development Strategy - Osuch-Rak, Ewa; Proczek, Magdalena (Studia Ecologiae et Bioethicae, 2016)
The concept of sustainable development can be defined and interpreted in many ways, but at its core lies an approach to development that balances different, and often competing, needs against an awareness of the environmental, social, and economic boundaries the society faces. The aim of the paper is to discuss the issue of turning the idea into practice, presenting environmental priorities of the EU’s Sustainable Development Strategy, their implementation and monitoring. The sustainable development indicators in the theme of climate change and energy, namely greenhouse gas emissions and primary energy consumption, are analyzed and described.